Development of an octree-based tool for generation of three-dimensional structure models using PSM approach - Carangan, Franz Marius R.; Quinay, Pher Errol B. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
To predict the response of a city in seismic events, tools that can provide relevant data (hazard-level, structure-level, agent response-level) for conducting quantitative damage estimations are needed. Area-based (damage estimation) approach is widely used in the Philippines, assisted by PHIVOLCS' Rapid Earthquake Damage Assessment System (REDAS) software in determining seismic hazards. Commercial analysis and design softwares, on the other hand, are used in vulnerability analysis. Physics-based approach is also a candidate for such objective but it is rarely used because utilizing this approach is difficult as its application to actual problems tends to be computationally expensive. To use this approach, model generation should be able to minimize computational cost and time. This research aims to develop a tool for automated generation of multiple resolution 3D structure models by applying OCTREE and Progressive Solid Models (PSMs). The developed tool is able to generate a series of structure models with varying resolution. An approach to selecting the optimal model resolution based on reduced number of degrees of freedom (DOFs) is also proposed. At the end, the models generated in this research are found to be able to represent the periods of oscillation of actual structures.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Earthquake hazard analysis; Three-dimensional modeling